Electroosmotic dewatering: an efficient method of sludge management - Jami, Mohammed Saedi; Iwata, Masashi; Tanaka, Takanori (2015)
The purpose of this work is to summarize our latest research results about constant- current electro-osmotic dewatering (EOD) as an efficient method for sludge management. The Terzaghi-Voigt combined model is used for the analysis of electroosmotic dewatering (EOD) of various solid-liquid systems by considering the creep deformation of materials. Bentonite clay, KC-flock, zinc oxide and some of their mixtures are used as experimental materials representing environmental sludge. It is assumed that the electro-osmotic pressure gradient Epg and modified consolidation coefficient Ce of the materials are constant. The relation between the ratio of creep deformation to total deformation B and the modified consolidation coefficient Ce is determined and compared with previous observations for the case of mechanical expression. The effectiveness of dewatering is analyzed based on operating parameters such as pre-consolidation pressure, material composition, electric current density and total solid volume per unit cross-sectional area. The model is verified by comparing the calculations with experimental data. The results show that Elecrtro-osmotic dewatering, as main solid-liquid separation process, is best applied for materials with permanent charge.